Strategi Pemasaran Syariah Pada Industri Rumahan Tempe Di Gang Saleh Plaju Dalam Meningkatkan Kesejahteraan Pelaku Usaha - Muthmainnah Nur Khoiriyah; Hilda Hilda; Muhammad Junestrada Diem (Jurnal Ekonomi dan Bisnis Digital, 2024)
Marketing strategies play a crucial role in achieving business success, making the marketing function vital in realizing business plans. To remain competitive and increase sales of products or services offered, a company must take action. By implementing successful marketing strategies and seizing opportunities to increase sales volume, companies can enhance or maintain their position in the market. This study aims to explore how entrepreneurs implement Islamic marketing strategies and their impact on improving their welfare. The study employs a qualitative method in the form of descriptive research. Data collection is carried out using observation, interrogation, and document collection methods. Data management involves data reduction, data presentation, and drawing conclusions. The results of this study indicate that entrepreneurs are already using Islamic Shariah-based marketing strategies similar to marketing mixes. These include: 1) product segmentation or distribution directly sold to consumers. 2) Target market, with varying consumer needs leading to product sales variation. 3) Position or reputation, entrepreneurs must maintain a good image by being respectful and having quality products. 4) Marketing tactics, utilizing differentiation so entrepreneurs have innovative developments in an ever-changing era. Entrepreneurs have already made processed products derived from tempeh. 5) Marketing values are halal and good, entrepreneurs have maintained product hygiene and some have halal certification. Traders in the Saleh alley are already included in prosperous society because they can fulfill all indicators of welfare improvement, namely physically in terms of daily clothing, food, and shelter needs, and spiritually by paying zakat, giving alms, charity, and sharing with orphanages.